(untitled) (Bangladesh Journal of Obstetrics & Gynaecology, 2019)
Background: Prevention of HPV infection by prophylactic vaccination is a critical step in reducing the cervical cancer burden. A pilot study was conducted to evaluate the serological immune response to the bHPV vaccine in adolescent Bangladeshi girls at 7th months of vaccination. This is the first in depth follow up study in Bangladesh to directly evaluate the long-term immunogenicity of the bHPV vaccine by measuring sustained HPV16/18 antibody titer seven years after vaccination. Objective: To determine the long-term immune response against HPV16/18 induced by the immunization with bivalent human papilloma virus (bHPV) 16/18 ASO4 adjuvanted vaccine by measuring the antigen specific antibody titer. Materials & Method: This was a cross- sectional observational study conducted among 30 adolescent Bangladeshi girls from October 2015 to September 2016 who were vaccinated with 3 doses of bHPV vaccine from December 2008 to June 2009 in the Division of Gynaecological Oncology of BSMMU. Antibody titer against bHPV 16/18 ASO4 adjuvanted cervical cancer vaccine was measured in the serum of the 30 vaccinee in the Virology laboratory of BSMMU using DRG HPV IgG ELISA (REF.EIA- 4907) kit. Data were analyzed by using SPSS version 21. Results: The mean age of the population was 17.9±1.2 years. Among 30 vaccinated subjects, vaccine-induced long-term anti-HPV ELISA seropositivity was 93.33% (with 95% CI) for both HPV 16/18 types measured at year seven post-vaccination. Immunization with the HPV16/18 L1 virus-like particle vaccine adjuvanted with AS04 induced sustained high levels of antibodies among adolescent Bangladeshi girls against high-risk HPV genotypes 16/18. Conclusion: Vaccination with bHPV is predicted to provide long-term protection against HPV infection and subsequent development of high-grade cervical lesions and cancer. Bangladesh J Obstet Gynaecol, 2019; Vol. 34(2): 72-78